Impacts of Climate Change on Dengue Risk in Brazil - Tatiane Menezes; Paula Pereda; Denisard Alves (European Regional Science Association (ERSA), 2014)
Climate has relevant impacts on human health. According to the World Health Organization (WHO), climate-sensitive health problems kill millions of people every year and undermine the physical and psychological health of millions (WHO, 2012). In the particular case of vector-borne diseases, climate conditions assure the vectors' survival and reproduction and, consequently, the transmission of the diseases (Kelly-Hope and Thomson, 2008). Increases in heat, precipitation, and humidity can allow insects to move from regions where infectious diseases thrive into new places. The vector-borne disease analyzed by this study is the dengue fever. Dengue fever is the key target infectious disease in Latin America, whose incidence depends highly on climate conditions due to the mosquitos. In this sense, this study intends to identify the climate impact on dengue in the country in order to measure the impact of climate change on the dengue risk in Brazil, and also examine the public policy's role on minimizing those effects in the country. The government influence, in terms of public policy, is mainly given by the universalization of running water and sewage collection (both urban infrastructure problems controlled by the municipal government), by the type of housing, educational measures, and by assuring the health assistance of the people affected by such diseases (availability of hospital beds, health expenditures). Pereda (2012) found out that integrated actions from local governments are needed to control the spread of the disease. In order to identify the climate impacts on dengue risk, a comparative case study research will be used, based on the comparison of cities that suffered from specific climate conditions that increased the risk of dengue with cities whose climatic conditions stayed the same. The counterfactual will be created based on the synthetic controls approach, which generates control groups as a combination of units not exposed to the intervention (Abadie and Gardeazabal, 2003; and extended by Abadie et al, 2010). Thus, the synthetic control is a weighted average of the available control units that sum to one. As Brazil is a wide country, and exposed to many climate patterns, there are many possibilities of gathering good control groups by using this methodology. The preliminary results suggest that the increase in temperature in temperate regions (South of the country) increase the incidence of dengue in the region. On the other hand, the increase in temperature in the tropical areas (North of the country) could diminish the disease. Therefore, due to the expected increase of temperatures in the future, the climate change might change the dengue fever distribution in the country. The study also intends to examine the public policy's role on minimizing those effects in the country, mainly focused on water supply and sanitation.
Keywords: I13; Q54; C10; R11; 330